PELATIHAN PENULISAN DAN PUBLIKASI ARTIKEL ILMIAH MENGGUNAKAN DIGITAL PLATFORM PADA MASA PANDEMI - Prahmana, Rully Charitas Indra; Lisnani, Lisnani (Jurnal Terapan Abdimas, 2022)
Abstract. Writing and publishing scientific articles are essential for researchers, lecturers, and students in Indonesia. However, many of them still have difficulty writing their research results in the form of scientific articles and publishing them in reputable international journals. So, this service activity is carried out to develop academic writing and publish scientific articles skills for researchers, lecturers, and students in Indonesia. The community service activities were carried out using a digital platform, namely Zoom Meeting, during the COVID-19 pandemic. The participants involved in this activity consisted of 193 participants, consisting of researchers, lecturers, and students from various regions in Indonesia. The collecting data uses a questionnaire which was analyzed descriptively. The activity results showed an increase in the participants' academic writing and publication skills, with an average increase of 71.45% after attending this training through a digital platform. The participants gained a lot of knowledge about academic writing and scientific publications in reputable international journals.  Abstrak. Keterampilan menulis dan menerbitkan artikel ilmiah sangat penting bagi para peneliti, dosen, dan mahasiswa di Indonesia. Namun, sejumlah dari mereka masih mengalami kesulitan dalam menuliskan hasil penelitian mereka dalam bentuk artikel ilmiah dan menerbitkannya pada Jurnal internasional bereputasi yang baik. Sehingga, kegiatan pengabdian ini dilakukan untuk menumbuhkan keterampilan menulis dan menerbitkan artikel ilmiah bagi para peneliti, dosen, dan mahasiswa di Indonesia. Adapun kegiatan pengabdian dilakukan menggunakan platform digital, yang bernama Zoom Meeting, pada saat masa pandemi COVID-19. Para peserta yang terlibat dalam kegiatan ini terdiri dari 193 peserta, yang terdiri dari peneliti, dosen, dan mahasiswa dari berbagai daerah di Indonesia. Pengumpulan data menggunakan kuesioner yang dianalisis secara deskriptif. Hasil pengabdian ini menunjukkan peningkatan keterampilan menulis dan publikasi para peserta dengan rata-rata peningkatan di angka 71,45%, setelah mereka mengikuti pelatihan ini melalui platform digital. Para peserta mendapatkan banyak pengetahuan tentang dunia penulisan dan publikasi ilmiah di jurnal internasional bereputasi yang baik.